LANGUAGE AS COGNITIVE AND DISCURSIVE PSYCHOMECHANICS OF CONSCIOUSNESS - Zasiekina, Larissa (Psychological Prospects Journal, 2014)
The results of theoretical and empirical research of language as main instrument of awareness acts of information and its reservation in the consciousness are highlighted in the article. It was revealed that correlation between language and consciousness is formed linguistic consciousness as mental reflection, generalization and transformation of environment by means of language. Language as psychomechanics of personality’s consciousness has cognitive (universal and genetic) and discursive (social and cultural) nature. Cognitive and discursive peculiarities of language as instrument of awareness are empirically revealed in cross-cultural studies. Since the main feature of consciousness is intentionality to find out functions for efficient objects use, the material of empirical study is represented by words meanings of objects based on their functions. Functions of objects in word meanings suggested by Ukrainian (n=25, 12 female and 13 male, mean age 21,7±3,0 years, Lesya Ukrainka Eastern European National Universities, Lutsk) and American (n=25, 15 female and 10 male, mean age 22,4±3,0 years, University of Central Arkansas, Conway, USA) students were analyzed. The results of empirical study allow establishing triads of functions: agentive, objective, individual; agentive, objective, collective; agentive, subjective, collective; agentive, subjective, individual; nonagentive, objective, individual; nonagentive, objective, collective; nonagentive, subjective, collective; nonagentive, subjective, individual. The distribution of the functions in the Ukrainian and American word meanings reveals cognitive (common for both cultures) and discursive peculiarities of the language. Cognitive peculiarities of the language are mental grammar, lexicon, brain activation, unawareness activity and intentionality of consciousness. Discursive peculiarities of language as psychomechanics of consciousness are characterized by predominance of nonagentive, subjective, individual functions among the American students and both agentive, subjective, individual and nonagentive, objective, collective functions among the Ukrainian students. Keywords: consciousness, linguistic conciseness, language, intentionality, psychomechanics, agentive / nonagentive, subjective / objective, individual / collective functions.